Comparison of corneal power measurement between Corneal Topography and Auto Ref/Keratometer - سعود, بتول; حبيب يوسف , (Latakia University Journal -Medical Sciences Series, 2023)
Abstract: Purpose: To compare corneal power measurements using Auto ref/keratometer(GR-3500KA) and corneal topography(SIRIUS). Methods: 87 eyes of 45 patients were included in this study. Flattest, steepest and average corneal powers were measured using corneal topography then auto ref/keratometer. The Intra Ocular Lens(IOL) power was measured using SRK-T formulae with steepest and flattest corneal powers measured by Sirius and GR-3500KA separately and the results were compared. We also studied the correlation between average central radius of curvature of anterior corneal surface, and the difference in average corneal power measurements between the two devices using Pearson correlation. Results: Mean steep corneal power using Auto Ref/Keratometer and Corneal Topography was: 43.98±1.07 and 43.85±1.09 diopters respectively, and the difference was statistically significant Mean flat corneal power using auto ref/keratometer and corneal topography was: 42.68±13.08 and 42.76±1.1 diopters respectively, and the difference was statistically significant . Mean average corneal power using auto ref/keratometer and corneal topography: 43.24±1.03 and 43.35±1.01 diopters respectively, and the difference was statistically significant. Mean IOL power(SRK-T) using steep and flat corneal powers obtained by Auto- ref/keratometer and corneal topography separately were: 19.20±3.6 and 19.32±3.5 diopters respectively, and the difference was statistically significant. Negative correlation was found between central average radius of curvature of anterior corneal surface, and the difference in average corneal power measurements. Conclusion: Auto Ref/Keratometer gives consistently higher measurements for corneal powers compared to corneal topography (SIRIUS). And such a difference does not significantly affect the IOL power. Key words: using Auto Ref/Keratometer, corneal power, corneal topography, IOL power.